The design and optimisation of nanophotonic devices using the Finite Element Method - Arca, Ahmet (2010)
The aim of this thesis is to develop a technique which can be used in the reliable modelling, design and optimisation of practical suboptical wavelength sized photonic/plasmonic devices, which may involve arbitrary geometries on various scales. The technique involves the application of numerical electromagnetic simulation led by theoretical knowledge and physical insight to determine, design and optimise the operating mechanism of such devices.